Evolution of the Deep Western Boundary Current inferred from 231Pa/230Th records - Süfke, Finn; Pöppelmeier, F.; Blaser, P.; Goepfert, T.; Regelous, Marcel; Gutjahr, Marcus; Gruetzner, Jens; Lippold, Jörg (2019)
As part of the Atlantic Meridional Overturning Circulation (AMOC) the Deep Western Boundary Current (DWBC) transports newly formed NADW southward along the North American continental rise representing the most important lower limb of modern AMOC. Resolving its evolution since the last glacial will drastically improve our understanding about the evolution of AMOC and its connection to (paleo)climate. For our investigations we sampled ODP sites 1059 - 1062 located on the Blake Bahama Outer Ridge (BBOR). The BBOR is ideally located within the modern flow path of the DWBC and is therefore well suited to record past changes in geometry and intensity of the DWBC. We applied the 231Pa/230Th kinematic circulation proxy on sediments from the BBOR that form a depth transect from 3000 to 4700 m water depth. In addition to sortable-silt data from the BBOR, which provide information mainly about changes in the very bottom current strength, the 231Pa/230Th kinematic circulation proxy provides a record of an integrated signal from the overlying water column. In combination with new εNd records from the very same samples, used for identifying the provenance of the prevailing water masses, our 231Pa/230Th records provide insight into past circulation states and the strength of the DWBC over the last 30 ka. Climatic key features such as the Last Glacial Maximum (LGM), deglaciation and Holocene in high-resolution are clearly resolvable. Both 231Pa/230Th and εNd indicate reduced circulation during the Younger Dryas and Heinrich Stadial 1 and 2 in agreement with records from the Bermuda Rise, including ODP site 1063. During the LGM circulation strength was slightly weaker compared to the deep and strong Holocene circulation but still active. With this new depth transect of combined proxy data we are able to reconstruct the intensity of the DWBC more robustly.